Deriving a patient de-identified clinical research database from an electronic health record system: A single center experience in determining the prognostic value of lactate, C-reactive protein, and procalcitonin in hospitalized patients. Issue 2 (2021) - Mohan, R; Ho, P; Dalton, L; Chan, F; Nguyen, HB
No abstract available